2013
DOI: 10.3892/ol.2013.1290
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin suppresses lipopolysaccharide-induced invasion by inhibiting matrix metalloproteinase-2/9 and increasing E-cadherin expression through extracellular signal-regulated kinase signaling in pancreatic cancer cells

Abstract: Invasion and metastasis are major factors in the poor prognosis of pancreatic cancer, which remains one of the most aggressive and lethal diseases worldwide. α-mangostin, a major xanthone compound identified in the pericarp of mangosteen (Garcinia mangostana, Linn; GML), possesses unique biological activities, including antioxidant, antitumor and anti-inflammatory effects. Whether α-mangostin is able to inhibit the invasive ability of pancreatic cancer cells has not been elucidated. In the present study, α-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
2
17
0
1
Order By: Relevance
“…MMP-9 degrades IV and V collagen and gelatin in the extracellular matrix, which facilitates the growth of tumor blood vessels to mesenchyme and subsequently, the microvessel density of tumor blood vessels increases, leading to continual tumor growth and distant metastasis (22). A previous study showed that the positive expression rate of MMP-9 is 50% in pancreatic cancer patients, and in cases accompanied by liver metastasis, the positive rate of MMP-9 expression is 66.7%, which indicates MMP-9 may be associated with pancreatic cancer liver metastases (23). The present study demonstrated that MMP-9 activity of human pancreatic cancer BXPC-3 cells was significantly reduced by paeoniflorin treatment, which is in agreement with the results of Lu et al (20) which indicated paeoniflorin inhibited the tumor invasion and metastasis of human hepatocellular cancer cells via suppression of MMP-9 and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 degrades IV and V collagen and gelatin in the extracellular matrix, which facilitates the growth of tumor blood vessels to mesenchyme and subsequently, the microvessel density of tumor blood vessels increases, leading to continual tumor growth and distant metastasis (22). A previous study showed that the positive expression rate of MMP-9 is 50% in pancreatic cancer patients, and in cases accompanied by liver metastasis, the positive rate of MMP-9 expression is 66.7%, which indicates MMP-9 may be associated with pancreatic cancer liver metastases (23). The present study demonstrated that MMP-9 activity of human pancreatic cancer BXPC-3 cells was significantly reduced by paeoniflorin treatment, which is in agreement with the results of Lu et al (20) which indicated paeoniflorin inhibited the tumor invasion and metastasis of human hepatocellular cancer cells via suppression of MMP-9 and ERK.…”
Section: Discussionmentioning
confidence: 99%
“…In human hepatoma SK-Hep-1 cells, α-mangostin leads to mitochondrial dependent apoptosis via inhibition of the p38 MAPK signaling pathway (84). In MIAPaCa-2 and BxPC-3 human pancreatic cancer cell lines, α-mangostin can suppress the invasion and metastasis of pancreatic cancer cells by decreasing MMP-2 and MMP-9 expression, increasing E-cadherin expression and inhibiting the ERK signaling pathway (85). In the PC-3 human prostate carcinoma cell line, α-mangostin can also inhibit metastasis of cancer cells through inhibition of MMP-2 and MMP-9 via the JNK signaling pathway (86).…”
Section: Xanthonementioning
confidence: 99%
“…In vitro and in vivo studies demonstrated that α-mangostin displayed a broad antitumor activity against various human cancer cells [9]. In addition, α-mangostin was able to induce apoptotic cell death in canine osteosarcoma D-17 cells [10] and inhibited metastasis of human cancer cells [11][12][13][14][15][16]. However, there was no data about the effect of α-mangostin on the MMP expression in human osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%